PRELIMINARY RESULTS OF BOTANICAL AND MICROBIOLOGICAL INVESTIGATIONS ON SEVERNAYA ZEMLYA 1995 (18th Symposium on Polar Biology) - / カンダ, ヒロシ; BOLTER, Manfred; KANDA, Hiroshi (National Institute of Polar Research, 1997)
P(論文) This paper describes preliminary results from an expedition to Severnaya Zemlya in August 1995. As visits to individual sites were short and the informations gained cannot be regarded as complete, they provided only preliminary data about the botanical and microbiological inventory from nine different sites. The landscapes can be described as polar deserts with only sparse vegetation. Soils show permafrost at levels less than 50 cm. A diverse pattern of vegetation, bacterial counts and bacterial biomass was found at small scales with respect to relief, hydrology and bird's nesting places. The pattern of bacterial counts and biomass is mostly related to content of organic matter, especially to plant cover. Higher plants occur at most places and their abundance can be regarded as indicators of colonization processes where glaciers retreated recently. departmental bulletin paper